Application of Goat Manure and Dolomite Fertilizer Doses on Chrysanthemum Growth and Yield - I Made Sukma Wardana; I Nengah Suaria; I Gusti Made Arjana (Agriwar Journal, 2026)
Chrysanthemum (Dendranthema grandiflora, Tzelev) is a high-value floricultural commodity with increasing market demand. This study aims to determine the effect of the dose of goat manure and dolomite fertilizer on the growth and yield of chrysanthemum plants, as well as to determine the most effective dose. The research was carried out in Pancasari Village, Sukasada District, Buleleng Regency, Bali, using a factorial Randomized Block Design (RBD) with two factors, namely the dose of goat manure (K1 = 5 tons ha-1, K2 = 10 tons ha-1, K3 = 15 tons ha-1) and the dose of dolomite fertilizer (D1 = 2 tons ha-1, D2 = 4 tons ha-1, D3 = 6 tons ha-1). The results showed that the interaction between the two treatments had no significant effect on the observed variables. Goat manure at a dose of 15 tons ha-1 (K3) produced the highest economic fresh flower weight of 43.77 g, an increase of 18.81% compared to the dose of 5 tons ha-1 (K1). Dolomite fertilizer at a dose of 6 tons ha-1 (D3) produced the highest flower stalk weight of 52.44 g. Goat manure and dolomite fertilizer applied separately each had a significant effect on the growth and yield of chrysanthemums.